Effect of seed protectants against pulse beetle on viability, vigour and health of cowpea seeds - Libi Antony A (Department of Seed Science and Technology, College of Horticulture, 2016)
Experiments to assess the effectiveness of seed protectants against cowpea pulse beetle (Callosobruchus spp.)and their impact on seed quality and seedling vigour of selected cowpea varieties were conducted at College of Horticulture, Vellanikkara during 2014-2016. Separate experiments were conducted for both Lola and Kanakamony varieties following a completely randomized design with 13 treatments and three replications. Seeds were treated with seed protectants viz. neem oil, castor oil, coconut oil, sweet flag rhizome powder, neem leaf powder, paanal leaf powder, karinotchi leaf powder, neem kernel powder, diatomaceous earth, rice husk ash, Beauveria bassiana and spinosad. Untreated seeds served as control. Both treated and untreated seeds were dried to nine per cent moisture content were stored under ambient conditions for a period of 13 months. The seed quality parameters like germination, speed of germination, seedling vigour indices, electrical conductivity of seed leachate, mortality of adult pulse beetles, number of eggs laid by beetle, egg hatchability and seed infestation were recorded at monthly intervals. Seed microflora infection per cent were recorded at start and end of storage period.The results revealed that germination and other seed quality parameters in both treated and untreated seeds decreased progressively over the storage period.However, irrespective of the variety, the seed protectants significantly enhanced the viability and quality of treated seeds. The quality of treated seeds was higher than that of untreated seeds for most part of the storage period. The germination in untreated seeds was retained above 75 per cent (the minimum seed certification standards (MSCS) required for cowpea) for eight months while it was retained for nine months in all treated seeds. The rate of decrease in seed germination and quality was slower in semitrailing variety Kanakamony compared to trailing variety Lola. In both the varieties, the germination was lower in untreated seeds in comparison to the treated seeds. Germination, speed of germination, seedling growth parameters and vigour indices were invariably high in seeds treated with neem based seed protectants viz., neem kernel powder, neem leaf powder and neem oil. Among the neem based botanicals used, seed treatment with neem kernel powder maintained higher germination and seed quality parameters viz., seedling shoot length, seedling root length, seedling dry weight and seedling vigour index I and II during storage. Similarly, the electrical conductivity of seed leachate and per cent infection by seed microflora was found to be consistently low in seeds treated with neem based botanicals, vegetable oils and spinosad.The efficacy of seed protectants against pulse beetle was evaluated at monthly intervals by recording weight of infested seed, seed infestation, mortality, fecundity and egg hatchability in twenty five seeds drawn randomly from each replication. The results revealed that all the seed protectants used were effective against pulse beetle during the initial period of storage and were significantly superior to control over the period of storage.Among the seed protectants evaluated, highest mortality of adult beetles,lowest fecundity, egg hatchability and seed infestation were recorded in seeds treated with spinosad followed by oils viz., neem oil, coconut oil and castor oil as well as other neem based botanicals. Seed treated with spinosad offered protection against pulse beetle for up to seven months of storage as evident from the cent per cent mortality of adult beetles, complete suppression of egg hatchability as well as low seed infestation in both varieties. Seeds treated with neem oil, castor oil, coconut oil, neem kernel powder and neem leaf powder recorded cent per cent mortality of adult beetles for five months of storage in both varieties. No seed infestation was recorded in seeds treated with neem oil, castor oil and coconut oil for up to five months of storage while a similar protection was offered by neem leaf powder and neem kernel powder for up to four months of storage. Spinosad was found to be the most effective in controlling pulse beetle infestation throughout the storage period. Based on the impact of seed protectants on seed viability, seedling performance as well as protection against pulse beetle infestation in cowpea, seed treatment with seed protectants viz., spinosad or neem based products (neem kernel powder, neem leaf powder and neem oil) or as oils (coconut oil and castor oil) can be recommended to be most effective in enhancing seed viability (by a period of one month over control), higher seed and seedling performance and protection from pulse beetle infestation and infection by microflora in cowpea. Among the above Spinosad can be recommended as the best seed treatment for cowpea if it can ensured that the treated seeds would be used only for seed purpose. However, in case the stored pulse seeds are meant for use as food, feed and seed, treatment with coconut oil could be recommended in place of neem based products since neem based botanicals are reported to cause sterility in humans and animals.